2016
DOI: 10.1242/jcs.184382
|View full text |Cite
|
Sign up to set email alerts
|

Organelle size control – increasing vacuole content activates SNAREs to augment organelle volume through homotypic fusion

Abstract: Cells control the size of their compartments relative to cell volume, but there is also size control within each organelle. Yeast vacuoles neither burst nor do they collapse into a ruffled morphology, indicating that the volume of the organellar envelope is adjusted to the amount of content. It is poorly understood how this adjustment is achieved. We show that the accumulating content of yeast vacuoles activates fusion of other vacuoles, thus increasing the volume-to-surface ratio. Synthesis of the dominant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 66 publications
(93 reference statements)
5
31
0
Order By: Relevance
“…This suggests that polyP levels of the cell are mainly controlled through synthesis and not through degradation. This interpretation is in line with our earlier findings showing that hyper-activation of the VTC complex by point mutations or overexpression of the regulatory subunit leads to higher polyP levels in vivo (Desfougeres et al, 2016a) and that the polyP content of vacuoles may be sensed and communicated to the cytosol (Desfougeres et al, 2016b). Studies on the mobilization of this store have so far been hampered by the fact that polyP turnover could be inhibited only partially because only a single vacuolar polyphosphatase was known.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This suggests that polyP levels of the cell are mainly controlled through synthesis and not through degradation. This interpretation is in line with our earlier findings showing that hyper-activation of the VTC complex by point mutations or overexpression of the regulatory subunit leads to higher polyP levels in vivo (Desfougeres et al, 2016a) and that the polyP content of vacuoles may be sensed and communicated to the cytosol (Desfougeres et al, 2016b). Studies on the mobilization of this store have so far been hampered by the fact that polyP turnover could be inhibited only partially because only a single vacuolar polyphosphatase was known.…”
Section: Discussionsupporting
confidence: 86%
“…The effect of Ppn2 was the strongest during early logarithmic phase, when ppn2Δ cells showed a clear shift towards longer chains. Taken together with previous observations (Desfougeres et al, 2016b), which suggested that the amount of polyP may be sensed inside the vacuole, our results suggest that polyP accumulation is mostly controlled by regulating the rate of the synthesis rather than degradation. In line with this, deletion of additional genes, such as (Table S1).…”
Section: Vacuolar Polyphosphatases Limit Chain Length But Not the Amosupporting
confidence: 89%
“…As a second strategy, yeast cells respond to osmotic challenges by fusing their vacuoles or fragmenting them into smaller units. This re‐adjusts the surface‐to‐volume ratio of the vacuoles (Brett & Merz, ; Desfougères et al , ), probably to avoid an overload of these hydrolytic compartments, which might lead to their lysis and presumably catastrophic consequences for the cells. Insufficient loading, on the other hand, might eliminate vacuolar membrane tension, which is a critical parameter for the functioning of many channels and transporters (Hamill & Martinac, ; Sukharev & Sachs, ).…”
Section: Discussionmentioning
confidence: 99%
“…Fusion is favored when vacuolar content increases, either by accumulation of macromolecules, e.g., during autophagy, or through osmotic water influx in hypotonic media. Fragmentation is triggered by lack of luminal content or hypertonic media (Bonangelino et al, 2002;Zieger & Mayer, 2012;Desfougères et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…The ADH1 promoter results in moderate overexpression. This explains the fusion of the vacuoles into a single larger organelle, which occurs as a consequence of enhanced polyP production (52). DIC, differential interference contrast.…”
Section: Vtc5 Is a Transmembrane Protein Localized In The Vacuolarmentioning
confidence: 98%